School Heads’ Accountability in School Management - Rose G. Pagunsan, Cherry; Moyani Jr., Gregorio (Polaris Global Journal of Scholarly Research and Trends, 2024)
School heads are considered persons in authority who manage the school and are considered the pillars of the educational system. Along with their authority, they are accountable for the outcomes of the school operations, programs, and projects. In this context, this paper determined the school heads’ levels of accountability in school management in a District, in a first-class municipality, in Negros Occidental during the School Year 2022-2023. Data needed for this descriptive study was collected from 133 respondents, mostly senior educators with bachelor's degrees, using a self-made survey questionnaire that passed the rigorous test of validity and reliability. The ensuing analysis showed school heads possessing a very high level of accountability in the domain of focusing on teaching and learning. However, in the domain of leading strategically, managing school operations and resources, developing self and others, and building connections, the level of accountability was observed to be high. The perception of school heads' accountability varied based on profile variables such as age, length of service, and highest educational attainment. Younger teachers and those with shorter length of service perceived higher levels of accountability. Moreover, teachers with lower educational attainment attributed higher levels of accountability across all domains. The findings of this study call for the school heads’ and those aspiring to become school heads to the importance of practicing accountability as leaders of the school, for more efficient and effective school leaders and eventually improve the level of school-based management.